Bioethics in human embryology: the double-edged sword of embryo research. (4th May 2022) - Anifandis, George; Sutovsky, Peter; Turek, Paul J.; Chavez, Shawn L.; Kunej, Tanja; Messini, Christina I.; Schon, Samantha B.; Mavroforou, Anna; Adashi, Eli Y.; Krawetz, Stephen A.
Abstract: There has been a significant increase in the use of assisted reproductive therapies (ARTs) over the past several decades, allowing many couples with infertility to conceive. Despite the achievements in this field, a mounting body of evidence concerning the epigenetic risks associated with ART interventions such as ovarian hormonal stimulation, intracytoplasmic sperm injection (ICSI), and in vitro culture (IVC) of oocytes and embryos has also emerged. Induced development of multiple follicles, the IVC media itself, and extended culture may alter the epigenome of both gametes and embryos, resulting in yet to be fully understood developmental, postnatal, and adult life health consequences. Investigators have attempted to decipher the molecular mechanisms mediating ART-induced epigenetic changes using either human samples or animal models with some success. As research in this field continues to expand, the ethical responsibilities of embryologists and researchers have become critically important. Here, we briefly discuss the ethical aspects of ART research, concentrating on the constraints arising from the perceived 'unnaturalness' of many of these procedures. Secondly, we focus on the bioethics and morality of human embryo research in general and how ethically acceptable model systems may be used to mimic early human embryogenesis. Lastly, we review the 14-day culture limit of human embryos and the notion that this rule could be considered of taken into account using new technologies and cues from animal models. The 'black box' of early post-implantation embryogenesis might be revealed using embryo models. As long as this distinct moral line has been drawn and closely followed, we should not fear scientific growth in embryo research. Although in vitro fertilization (IVF) is ethically acceptable, research with human embryos to improve its success raises serious ethical concerns that are in need of constant revisiting. Glossary index: Moral status: the ascription of obligations and rights to embryos on the basis of sentience; Sentience: the capacity of the developing embryo to experience feelings and sensations, such as the awareness of pain; Ectogenesis: the growth of the embryo in an artificial environment outside the mother's body.